2020
DOI: 10.3390/nu12041088
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and Risks of Cardiovascular Diseases: An Umbrella Review

Abstract: Unhealthy diet is a significant risk factor for cardiovascular diseases (CVD). Therefore, this umbrella review aims to comprehensively review the effects of dietary factors, including dietary patterns, food groups, and nutrients on CVD risks. Medline and Scopus databases were searched through March 2020. Systematic reviews with meta-analyses (SRMA) of randomized controlled trials (RCTs) or observational studies measuring the effects of dietary factors on CVD risks were eligible. Fifty-four SRMAs, including 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 73 publications
(117 reference statements)
1
67
0
3
Order By: Relevance
“…Regarding CVD risk, a recent meta-analysis of cohort studies found the borderline effect of dietary total fat, saturated fatty acid (SFA), monounsaturated fatty acid (MUFA), and FUFA, with HRs (95% CIs) of 0.97 (0.93-1.01) (N = 45), 0.97 (0.93-1.02) (N = 56), 0.97 (0.93-1.01) (N = 43), and 0.97 (0.93-1.00) (N = 45) (Zhu, Bo, & Liu, 2019). Among FUFAs, n-3 FUFA was found to significantly reduce the risk of CVD, with RRs (95% CIs) ranging between 0.89 (0.82-0.98) to 0.90 (0.85-0.96), whereas findings for n-6 FUFA and total FUFAs did not reach the consistency in the umbrella review (Chareonrungrueangchai, Wongkawinwoot, Anothaisintawee, & Reutrakul, 2020). Pooled estimates from another meta-analysis found that n-3 FUFA supplementation was associated with lower risks of coronary heart disease (RR = 0.90, 95% CI = 0.85-0.96) and myocardial infarction (RR = 0.89, 95% CI = 0.80-0.99), but not for total CVD (RR = 0.98, 95% CI = 0.95-1.01) and stroke (RR = 0.88, 95% CI = 0.71-1.10) (Hoang & Kim, 2020).…”
Section: Fatty Acidsmentioning
confidence: 85%
“…Regarding CVD risk, a recent meta-analysis of cohort studies found the borderline effect of dietary total fat, saturated fatty acid (SFA), monounsaturated fatty acid (MUFA), and FUFA, with HRs (95% CIs) of 0.97 (0.93-1.01) (N = 45), 0.97 (0.93-1.02) (N = 56), 0.97 (0.93-1.01) (N = 43), and 0.97 (0.93-1.00) (N = 45) (Zhu, Bo, & Liu, 2019). Among FUFAs, n-3 FUFA was found to significantly reduce the risk of CVD, with RRs (95% CIs) ranging between 0.89 (0.82-0.98) to 0.90 (0.85-0.96), whereas findings for n-6 FUFA and total FUFAs did not reach the consistency in the umbrella review (Chareonrungrueangchai, Wongkawinwoot, Anothaisintawee, & Reutrakul, 2020). Pooled estimates from another meta-analysis found that n-3 FUFA supplementation was associated with lower risks of coronary heart disease (RR = 0.90, 95% CI = 0.85-0.96) and myocardial infarction (RR = 0.89, 95% CI = 0.80-0.99), but not for total CVD (RR = 0.98, 95% CI = 0.95-1.01) and stroke (RR = 0.88, 95% CI = 0.71-1.10) (Hoang & Kim, 2020).…”
Section: Fatty Acidsmentioning
confidence: 85%
“…A healthy diet has been found to exert beneficial effects on cardiovascular disease (CVD) prevention [ 53 , 54 , 55 ]. The diet quality was associated with CVD-free life expectancy [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper thoroughly reviewed the effects of foods and nutrients in different dietary scenarios according to CVD risk outcomes, presenting the inconsistent results [52]. It points out many obstacles toward quantification of dietary effects on CVD outcomes.…”
Section: Discussionmentioning
confidence: 99%